Capacidade contributiva na recuperação judicial e na falência - Santos, Marivaldo Andrade dos (2024)
Contributory capacity (ability to contribute) represents one of the pillars on which the main institutes of Tax Law are based, considering that it is a true intermediation mechanism between the demands of the Tax State and the real economic conditions of the taxpayer. And it is exactly this intermediate position that makes it a particularly relevant instrument for discussing the possibility of intercession between tax formulations and operations and the debtor's pre bankruptcy and bankruptcy stages. Based on the establishment of this fundamental premise, the objective of this research is to debate the contributory capacity as a means that transcends the limits commonly pre-established by the doctrine. Traditionally, the ability to contribute is understood, interpreted and applied as a principle that the legislator uses to calibrate the tax burden, in order to prevent the subject from having to bear a financial burden that is too much greater than what they actually enjoy. It turns out that there is a pressing demand around the feasibility of the contributory capacity becoming a safeguard tool for taxpayers who are in a state of fiscal vulnerability both at the time of judicial recovery and at the time of bankruptcy itself. In summary, discussing a topic of this magnitude only becomes viable if the following aspects are considered: (i) the theoretical rigors that guide the contributory capacity must be made more flexible, as a way of giving way to an interdisciplinary program between Tax Law and (pre)bankruptcy law; (ii) the contributory capacity must be assessed from a socio-tax perspective; (iii) the conceptual dimension of contributory capacity needs to be reassessed as a way of raising it to the status of an indispensable element for proposing new ways of recovering public credit in the company's judicial recovery phase and (iv) the satisfaction of normative objectives informing the pre-bankruptcy and bankruptcy legal regime require a stance consistent with the pragmatic purposes of contributory capacity